PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING - Irwan Suhendra; Firman; Desyandri (STKIP Subang, 2024)
The purpose of this study is to improve the learning outcomes of mathematics through the use of discovery learning models in fourth grade students of SD Negeri 15 Muara Siberut semester 1 of the 2023/2024 academic year. The design of this study is classroom action research (CAR). The research variable is the independent variable discovery learning model and the dependent variable the results of learning mathematics students. Data collection techniques by means of observation and evaluation, instruments of data collection with observation sheets, written tests and multiple choice. Quantitative data analysis (learning outcomes) and qualitative techniques. The results showed an increase in mathematics learning outcomes of fourth grade students of SD Negeri 13 Muara South Siberut Subdistrict, Kepulauan Mentawai Regency, first semester of 2022/2023 academic year after discovery learning model action. Before the action, 7 students (30%) were completed. After being given action in the first cycle, there was an increase in the number of complete students to 14 (61%) in the second cycle there was an increase in the number of completed students to 21 (91%).